Penerapan Aplikasi Digital Amartya Berbasis Saas sebagai Strategi Peningkatan Pendapatan UMKM di Kota Semarang dalam Ekonomi Berkelanjutan - Radite Ranggi Ananta; Alvito Surya Nugraha; Irsyad Zidan Ar Rifqi (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
This research explores the impact of using the application on Micro, Small, and Medium Enterprises (MSMEs) in the city of Semarang in the context of digitalization and the implementation of Artificial Intelligence. (AI). Research data were obtained from a survey of 100 MSME actors and in-depth interviews. The analysis method used is qualitative descriptive. The research results indicate that the application can potentially enhance MSMEs' operational and marketing efficiency through a digital system. However, it still faces the challenge of low digital literacy among MSME actors. The discussion shows that this innovation can improve the competitiveness of business actors in the digital era, especially in understanding consumer behavior and logistics management. The research conclusion emphasizes that implementing the application can be a solution to increase MSME income, help them adapt to market changes, and effectively utilize digital technology.